Sakura Hime : the legend of Princess Sakura 11 - Tanemura, Arina; Miyaki, Tetsuichiro (VIZ Media, 2013)
"Kohaku follows Hayate into the woods and finds him there with Rurijo. Enju also witnesses the clandestine meeting and confronts Rurijo about her betrayal. Rurijo, now abandoned by Enju, vows to kill Princess Sakura" -- from publisher's web site.